The Correlation of Self-Leadership and Autonomy Among Students of Theological College in North Sumatera - Johanes Waldes Hasugian; May Rauli Simamora; Nasib Tua Lumban Gaol (Budapest International Research and Critics University, 2021)
College Students entering higher education will form new habits and require efforts to adjust to the demands of autonomy. Self-leadership is one of the adjustment strategies needed to achieve autonomy. This study aims to find out the relationship between self-leadership and student autonomy. The subject of the study was 211 college students of Theological College in North Sumatra. The data was collected using two scales, namely a self-leadership scale of 34 items with a α = 0.91 and an autonomy scale of 30 items with a α = 0.87. Pearson Product Moment's correlational analysis showed a correlation value of 0.679 with sig. (2-tailed) = 0.000 (p<0.01) which means there is a very significant positive relationship between self-leadership and autonomy. Students who develop self-leadership strategies, namely behavior-focused strategies, natural reward strategies constructive thought strategies will be able to direct themselves in acting as they see fit, making their own decisions and accounting for their own behavior. The coefficient of determination of R Square is 0.462 which means the percentage of self-leadership variable contribution to increased autonomy is 46.2% and 53.8% is the contribution of other variables. The motivation and environment of students, the character of the tasks given, the competence of teaching lecturers, and the materials or courses taken by students may be able to contribute in student autonomy to the reach of academic achievement.